2017
DOI: 10.5114/aic.2017.66186
|View full text |Cite
|
Sign up to set email alerts
|

Twelve months follow-up after retrograde recanalization of superficial femoral artery chronic total occlusion

Abstract: IntroductionFifty percent of cases of peripheral artery disease are caused by chronic total occlusion (CTO) of the superficial femoral artery (SFA). Ten–fifteen percent of percutaneous SFA recanalization procedures are unsuccessful. In those cases the retrograde technique can increase the success rate of the procedure, but the long-term follow-up of such procedures is still unknown.AimTo assess the efficacy and clinical outcomes during long-term follow-up after retrograde recanalization of the SFA.Material and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…Nevertheless, there are still scarce data on large populations that estimate the predictors of long-term treatment results in this group of patients, especially those treated from the retrograde approach. In the current study, the mortality after 36 months of follow-up was 13.4%, which was relatively low compared to previous publications, where mortality in the overall group of patients with PAD treated with endovascular interventions reached 6–50% with a similar mean age of participants to the current study at baseline and depended on the length of follow-up [1315]. However, compared to previous studies, the rate of CKD was lower, impacting the mortality.…”
Section: Discussioncontrasting
confidence: 50%
“…Nevertheless, there are still scarce data on large populations that estimate the predictors of long-term treatment results in this group of patients, especially those treated from the retrograde approach. In the current study, the mortality after 36 months of follow-up was 13.4%, which was relatively low compared to previous publications, where mortality in the overall group of patients with PAD treated with endovascular interventions reached 6–50% with a similar mean age of participants to the current study at baseline and depended on the length of follow-up [1315]. However, compared to previous studies, the rate of CKD was lower, impacting the mortality.…”
Section: Discussioncontrasting
confidence: 50%
“…Endovascular treatment of the superficial femoral artery (SFA) has been successfully performed as an alternative to surgery for a long time [ 1 ]. It has been demonstrated that use of the stents in the SFA has a high procedural success and less complications [ 2 ]. Although there have been advances in the peripheral stent technology in recent times, the most important issue of the stenting is still in-stent restenosis in long-term follow-up, and its treatment is difficult [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 The use of a retrograde approach in recanalization of atherosclerotic occlusions has already been reported in the treatment of occlusions of the superior femoral artery after the failure of the ipsi-or contralateral femoral approach. 12,13 Indeed, histopathological features of atherosclerotic occlusions suggest a more favorable condition in the retrograde recanalization. Atherosclerotic occlusions often have a proximal fibrous cape with a tapered convex shape, pushing the guidewire peripherally into the subintimal space.…”
Section: Discussionmentioning
confidence: 99%